Project Diary as a Strategy of Urban Apprehension: The Case Study of Thessaloniki - Prevedello, André Augusto (Writingplace, 2023)
This article is part of the strategy of understanding the urban fabric of Thessaloniki through a project diary composed of sketches, photographs, and local research of the urban evolution of the city. It was produced along a whole month with the objective of supporting urban planning proposals for the S.O.S. – Sustainable Open Solutions for European urban waterfronts programme, in January/February of 2022. The working method (in action investigation) produced important results de-rationalizing the planning process and stimulating new ways of thinking about contemporary urban problems. In a time when authors talk about the death of humanism, because there are no more ties that can keep society united, the article propose here an exercise in which progressive and rational thinking for urban planning methodologies are not the protagonist.